Antimicrobial resistance, serogroups, virulence gene profiles and MLST of Escherichia coli from giant panda - Li, Mingxi; Lv, Ruiqing; Li, Xiaowei; Song, Chao; Xingxin, Liang; Zhang, Huanrong (Frontiers in Microbiology, 2024)
Escherichia coli is a major bacterial pathogen which causes diarrhea in the giant panda.This study investigated the biological characteristics of 100 E. coli strains isolated from fecal samples collected from 100 captive giant pandas of different age groups and sexes. A standard Kirby-Bauer disk diffusion antimicrobial susceptibility test was performed with the isolates and we then further evaluated the antibiotic resistance genes (ARGs) by high-throughput quantitative PCR. Additionally, we then analyzed O serogroups through a slide agglutination test, virulence genes and the multi-locus sequence typing (MLST) by PCR. Antimicrobial susceptibility testing demonstrated that the 100 E. coli strains were mainly resistant to ENR (68%), AM (56%), IPM (55%), AMX (54%) and CA (52%), but were susceptible to MEM and FOX. The resistance to TZP, AK, FEP, CAZ, AMS, AZM, AT and IPM was significantly related to age (P < 0.05); the resistance rate of E. coli isolated from female giant pandas to N was significantly higher than in males (P < 0.05). Forty-five different types of ARGs were found, which included a total of 2258 ARGs, in the 100 E. coli isolates. The top ten of detection rate of ARGs were: acrA-04, aacC, blaTEM, sul2, blaOXY, ARGs aac (6')I1, blaCTX-M-03, tetD-02, blaSHV-02 and blaOXY were significantly related to age (P < 0.05), blaSHV-02, blaNDM and ampC-04 were related to sex (P < 0.05). Twelve different O serogroups from 32 E.